Life-Threatening Pancreatitis in Jehovah's Witness Patients With Severe Anemia Treated Without Transfusions and by Interventional Radiology Techniques. (February 2019) - Kishi, Patrick; vanSonnenberg, Eric; Stroker, Misa
Blood transfusions in anemic patients frequently are used for critically ill patients as a life-saving therapeutic maneuver. Jehovah's Witness (JW) patients typically refuse blood transfusions due to religious beliefs. Numerous clinical reports, in a wide spectrum of medical specialties, have shown no greater morbidity or mortality in JW patients or others who refused transfusions compared to those patients who accept transfusions. We report our experience with two JW patients who presented with severe anemia and life-threatening pancreatitis. Despite undergoing percutaneous drainages by interventional radiology (IR) for complex pancreatic collections (and other IR drainages), neither patient suffered any adverse effect from the IR procedures, even though they refused blood transfusions. Our experience suggests that IR procedures also may be successful with this more limited blood product protocol.